ТАЪЛИМДА БЎЛАЖАК ЎҚИТУВЧИЛАРНИ ТАЙЁРЛАШДА РАҚАМЛИ ТЕХНОЛОГИЯЛАРНИ ЎҚИТИШНИНГ ЎЗИГА ХОС АСПЕКТЛАРИ - Ильясова, З.К. (SCIENCE and SOCIETY, 2023)
The article deals with the issues of developing ideas about computer technologies as a science in education, building one's own field of science, a new educational paradigm, which impose new requirements on the training of future teachers. Based on the analysis, the problems of teaching digital technologies in education in pedagogical universities are identified, and general recommendations are proposed on the content and organization of the educational process.
Keywords: education; digital technologies; computer studies; universal learning activity; problems of teaching computer science; problems of its content and organiza tion of its educational process; fundamental